Relationship between Mechanical Properties and Height-Diameter Ratio of Moso Bamboo - Liming Yang; Yan Yuan; Xiaoming Lu (BioResources, 2024)
Systematic tests of longitudinal compression, bending, longitudinal shear, and longitudinal tensile strength of bamboo were conducted to study the variation of mechanical properties and the height-diameter ratio of bamboo. The predictive relations of mechanical properties and height-diameter ratio were fitted by linear regression analysis. The results showed that the mechanical properties of longitudinal compression, bending, longitudinal shear, and longitudinal tensile strength of bamboo increased with the increase of the height-diameter ratio. In this paper, the method of deducing the relationship between mechanical properties and height-diameter ratio of bamboo through the linear fitting relationship between mechanical properties and height-diameter ratio was shown to have high applicability and accuracy for bamboo. This paper has a certain reference value for the evaluation of mechanical properties of bamboo and has a certain practical value for reducing the testing cost.